PERBANDINGAN DAYA SIMPAN DAN UJI ORGANOLEPTIK MIE BASAH DARI BERBAGAI MACAM BAHAN ALAMI - Ria Dwi Jayati; Sepriyaningsih S; Silvia Agustina (LP4MK STKIP PGRI Lubuklinggau, 2018)
This study aims to determine the ratio of storability and organoleptic test of Natural Ingredients used to preserve wet noodles. The type of this research is qualitative descriptive research. The object of this research is wet noodles mixed with carrot juice, pampkin juice and turmeric juice. Data were collected through observation of shelf life for 8 days storage and organoleptic test against 50 panel of consumption panel. The result of the research shows that there is a comparison of storage power of each added juice. The conclusion of this research is the treatment with the longest shelf life that is for 8 day that is wet noodle which is added with carrot juice (P1), while for the fastest storage which is wet noodle is treatment P0 (control) for 1 day. The results of organoleptic test from wet noodles to the most acceptable power are wet noodles with the addition of pumpkin juice (P2).